Magnetic GAA (MAG-GAA) for Vertical and Horizontal Magnetic Field Detection - Khine Thandar Nyunt Swe; Amporn Poyai; Toempong Phetchakul (My University, 2024)
The Gate All Around (GAA) is introduced as a magnetic sensor to sense the vertical and horizontal magnetic field applied to the device. Magnetic GAA (MAG-GAA) consisting of one source contact, one gate contact wrapped around the channel, and four drain contacts are created and simulated for the two-dimensional magnetic field detection using Sentaurus. The proposed device structure of MAG-GAA is designed and operated based on the current mode of the Hall effect. The vertical magnetic field is sensed by activating the drain contacts D1 and D2. To detect the horizontal magnetic field, the drain contacts D3 and D4 positioned at the top and bottom surfaces of the device are enabled. The differential drain current is obtained as the magnetic response in both detections. MAG-GAA in which the channel length and width are 10 nm and 5 nm respectively is simulated by applying the magnetic field 0.1 T, 0.2 T, 0.3 T, 0.4 T, and 0.5 T in +z, -z, +y, and -y directions. Their respective magnetic responses are illustrated, and the Hall current reaches the highest value at the magnitude of the magnetic field 0.5 T in both cases of magnetic field detection. The sensitivity of MAG-GAA for vertical magnetic field detection is better than its sensitivity for the horizontal magnetic field.
Keywords: Magnetic Field Sensors Techniques; Magnetic properties of thin films; Atomic and Subatomic Physics Research